OCEANS 2016 MTS/IEEE Monterey 2016
DOI: 10.1109/oceans.2016.7761007
|View full text |Cite
|
Sign up to set email alerts
|

Mooring systems for marine energy converters

Abstract: This paper discusses several new technologies for mooring floating marine energy converter (MEC) devices, such as wave energy generators, tidal current turbines and floating wind turbines.The principal mooring component is a special nylon fiber rope which provides cyclic tension fatigue endurance much superior to that of conventional nylon ropes. The nylon fiber is treated with a new proprietary coating which has excellent wet yarn abrasion properties. The parallel-subrope type rope construction further reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The results from yarn-on-yarn loading abrasion tests show a significant increase in abrasion resistance by the addition of a specially developed coating. Furthermore, the long lay length rope construction enables these polyamide ropes to exhibit very good fatigue performance, similar to that demonstrated recently for another rope product by Ridge et al (2010;Banfield, 2017;Flory, 2016) .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The results from yarn-on-yarn loading abrasion tests show a significant increase in abrasion resistance by the addition of a specially developed coating. Furthermore, the long lay length rope construction enables these polyamide ropes to exhibit very good fatigue performance, similar to that demonstrated recently for another rope product by Ridge et al (2010;Banfield, 2017;Flory, 2016) .…”
Section: Resultssupporting
confidence: 77%
“…There is a widely perceived idea that polyester ropes have superior fatigue resistance than nylon ropes. Quite recently, however, Ridge et al (2010;Banfield, 2017) have shown significantly improved fatigue results for twisted nylon ropes; those authors qualified these ropes as ideal for wave energy convertor moorings and Flory et al (2016) also discussed these applications. Two major differences compared to the earlier fatigue work were the use of twisted ropes with long lay lengths and the application of improved fibre coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Taut-synthetic systems provide restoring force to the platform by the elastic properties of the rope [3]. By comparison a chain catenary system provides restoring force through the geometry of the mooring system and the weight of the chain [4]. For a chain catenary system to be functional in the intermediate depths a large amount of chain needs to be used to provide the necessary restoring force for the platform.…”
Section: Introductionmentioning
confidence: 99%
“…Mooring systems of dynamic floating MRE devices are required to provide effective station-keeping whilst reducing the combined effects of metocean loads on the system. Conventional station-keeping solutions, composed of steel wire and chain systems, fail to provide the necessary compliance to minimise peak loads for a highly dynamic system (Flory, JF;Banfield, SJ;Ridge, 2016). This reduces system reliability, where a mooring component failure may lead to interruption of operations and incur high offshore repair costs.…”
Section: Introductionmentioning
confidence: 99%